Laparoscopic Living Donor Right Hepatectomy Regarding the Anatomical Variation of the Portal Vein: A Propensity Score–Matched Analysis. Issue 7 (24th June 2021) - Rhu, Jinsoo; Kim, Mi Seung; Choi, Gyu‐Seong; Kim, Jong Man; Kwon, Choon Hyuck David; Joh, Jae‐Won
Abstract : This study is designed to analyze the feasibility of laparoscopic living donor right hemihepatectomy in living donors with portal vein variation. Living donor liver transplantation cases using a right liver graft during the period of January 2014 to September 2019 were included. Computed tomographic angiographies of the donor were 3‐dimensionally reconstructed, and the anatomical variation of the portal vein was classified. To reduce selection bias, a 1:1 ratio propensity score–matched analysis between the laparoscopy group and the open group was performed. Surgical and recovery‐related outcomes as well as portal vein complication‐free survival, graft survival, and overall survival rates were analyzed. After matching, 171 cases in each group from 444 original cases were compared. The laparoscopy group had a shorter operation time ( P  < 0.001), a smaller number of additional opioids required by the donor ( P  < 0.001), and a shorter hospital stay ( P  < 0.001). There were no differences in the portal vein complication‐free survival ( P  = 0.16), graft survival ( P  = 0.26), or overall survival rates ( P  = 0.53). Although portal vein complication‐free survival was inferior in portal veins other than type I ( P  = 0.01), the laparoscopy group showed similar portal vein complication‐free survival regardless of the anatomical variation of portal vein ( P  = 0.35 in type I and P  = 0.30 in other types). Laparoscopic living donor right hemihepatectomy can be performed as safely as open surgery regardless of the anatomical variation of the portal vein. Abstract : https://www.wileyhealthlearning.com/Activity2/7395821/Activity.aspx